A Long Journey of Historical Research and Scientific Publication - Purnawan Basundoro (Diponegoro University, 2021)
This paper describes the steps of historical research as well as the possibility of publishing the results in international journals. Historical research is an attempt to reconstruct various events in the past in the form of stories that can be read again by the wider community. The main problem faced in writing historical articles is usually related to relevance. Relevance in historical writing means that historical narratives are written suggested to have links or affinity with contemporary conditions. If the historical narrative presented has no relevance to the present, it is considered to have low use value for the reader. Historical research starts from the process of finding sources or what is known as heuristics. Some historians consider written sources as the main sources, even though there are alternative sources that are no less important, namely oral sources that have the same value and use as written sources. Historians are also required to publish their research results in journals, especially in international journals. Publication is considered as a manifestation of the responsibility of researchers to the wider community. This paper was written using the literature study method. The sources of the literature are read, analyzed for their contents, and become a reference in writing this paper.